Evaluation of the meat quality and muscle fiber traits of buffaloes - De Lima Francisco, Caroline [UNESP] (2010)
The aim of this study was to evaluate Myosin Heavy Chain Isoforms (MyHC) of the muscle fiber types and relationship with different parameters of quality in Longissimus dorsi muscle (LD) of 28 not-castrated Mediterranean buffaloes slaughtered in different weights (450, 480, 510 and 540 kg). Samples of the LD were collected between 12-13tn ribs and submitted to the techniques of electrophoresis (SDS-PAGE), alkaline m-ATPase and evaluations to the qualitative characteristics, color (Co), marbling (Mrb) and shear force (SF). Relative percentage of isoforms (%MyHC IIa, %MyHC IIx/d, %MyHC I) as well as muscle fiber frequency (Ffast, Fslow), area (Afast, Aslow) and diameter (Dfast, Dslow) were measured. It was possible to observe alterations in the water buffalo meat quality according to the changes that occurred in muscle fiber types influenced by the increase of the slaughter weight. Correlation was evidenced (P < 0.05) between the slaughter weight and the parameters %MyHC IIa (r = -0.51), %MyHC IIx/d (r = 0.38), Ffast (r = -0.63), Fslow (r = 0.63), Afast (r = 0.79), Aslow (r = 0.87), Dslow (r = 0.38), Mrb (r = 0.34) and SF (r = 0.70). The variable Mrb and SF were correlated positively (P < 0.05) with the Aslow (r = 0.42; r = 0.68, respectively). Meat color was influenced by the slow fiber diameter (r = 0.39; P < 0.05). The meat tenderness found in this experiment is related to the area of muscle fiber types.